SENSORY EXPERT: DEVICE FOR SENSORY TEST - MOHD ADZMI, MOHD DANIAL AIMAN (2018)
This paper proposes an integrated device for somatosensory assessment specifically for assessing humans’ heat nerves. The device is moving towards Internet of Things (IoT) where the compact sized and easy to carry device can be used to monitor the condition of patients’ heat nerves system before and after they are having their somatosensory treatment. The device can show visual results via the Blynk application for assessing the condition of nerves system and store data to the email for historical references. The study is divided into three stages which are developing heating element stage, developing algorithm for heat sensing stage and developing algorithm for data transmitting stage. In the study, the concept of creating heating element is by varying the current flows into the peltier module by using Force Sensitive resistive (FSR) sensor but it is find that the amount of current flows into the peltier module is very low which causes circuit switching method is implemented by using three poles four throw switch with different type of resistors in the circuit. In developing the algorithm for heat sensing, humidity and temperature sensor DHT 11 is used and the data of temperature is displayed in Blynk applications. The data is then sent to a Gmail as a storage by developing algorithm in Wi-Fi module NodeMCU ESP8266. As conclusion, further study in developing the heating element is needed to ensure that the device can work with optimal power supply and the desired cooling temperature can be achieved.